A field investigation of a solar-powered adsorption cooling system under Guangzhou's climate with various numbers of heat exchangers in the adsorbers. (17th November 2017) - Zhu, Long Qian; Tso, Chi Yan; He, Wei; Wu, Chi Li; Chao, Christopher Y.H.
Abstract : In the current study, a solar-powered double-bed adsorption cooling system has been built and tested in the Guangzhou climate. The effect of the pre-heating process on the cooling performance of the adsorption cooling system powered by solar energy has been experimentally investigated. A specific cooling power of 52.2 W/kg and a coefficient of performance of 0.20 were achieved under a 2-h pre-heating process with operating conditions of 26°C cooling water inlet temperature, 16°C chilled water inlet temperature, 8 L/min hot water and cooling water flow rate, 2 L/min chilled water flow rate and 600 s adsorption/desorption phase time. The average specific cooling power and coefficient of performance were improved by 26.1% and 33.3%, respectively, as compared to the case without conducting the pre-heating process. In addition, the influence of dead volume on the specific cooling power and coefficient of performance of the adsorption cooling system has also been investigated. Using various numbers of heat exchangers in the adsorber achieved different values of adsorber dead volume. The results show that a higher specific cooling power value is obtained with a smaller dead volume. Finally, the cooling performance of the adsorption cooling system was also studied under various operating conditions and a maximum specific cooling power and coefficient of performance are 180.4 W/kg and 0.29, respectively.